Effect of a Pilot Programme by Capability Approach to Prevent Lifestyle-related Diseases in Kaski, Nepal - Thapa, Yoko Oda; Poudel, Janak; Acharya, Prakash; Kimura, Kenji; Kawata, Rina; Kanzaki, Maki; Okugawa, Hiroko; Sakai, Hiroko (Journal of Health Promotion, 2020)
In the rural area of Nepal, lifestyle-related non-communicable diseases (NCDs) are emerging in recent days. We piloted a program model (2017-2019) to protect people from lifestyle-related diseases in a remote village of Kaski district where the health facilities are limited. This program was supported by Japan International Corporation Agency. We aimed to initiate a simple model of health monitoring to reduce the risks of lifestyle-related diseases. Health monitoring (blood pressure and body weight measurement) together with peer education regarding lifestyle-related disease was conducted by trained volunteers on regular bases. One-group pre-test–post-test research design was used to measure the impact of the program on the 104 participants with the age ranging 52±8.99 years in female and 57±7.38 years in male, sampled from the 100 households in the target village, Gairegaon. The double burden of underweight and overweight was observed in the programming community. After the program was conducted for one year, the percentage of people who is in the normal body mass index (BMI) range was significantly increased from 68.2% to 75.9% in total. Similarly, the ratio of normal blood pressure rose up significantly from 40.4% to 59.6%. This program results suggested that the community-led capability approach works effectively with locally affordable cost to change the behavior of people to reduce the risk of lifestyle-related diseases.